Prevalence and incidence of chemotherapy-induced taste alterations in adult cancer patients: a systematic review protocol. Issue 5 (23rd May 2022) - Corremans, Marleen; Mortelmans, Dimitri; Geurden, Bart; Luyten, Sarah; Bekkering, Geertruida
ABSTRACT: Objective: This study will synthesize the available evidence on the prevalence and incidence of chemotherapy-induced taste alterations in adult cancer patients. Introduction: Taste and smell alterations in cancer patients due to chemotherapy affect patients' quality of life and can cause malnutrition. Recent knowledge about the incidence and prevalence of chemotherapy-induced taste alterations may enable tailored food interventions for this specific population. Describing variations in taste changes in subgroups of chemotherapy is important to inform taste steering interventions. Inclusion criteria: The review will consider studies that include adult cancer patients who are receiving or have received chemotherapy as a treatment for an oncologic issue. It will include studies that investigate the prevalence and incidence of chemotherapy-induced taste alterations that have been assessed objectively or subjectively by patient-reported outcomes. Methods: A systematic search will be performed of the following databases: MEDLINE (PubMed), CINAHL (Ovid), Embase, and OpenSIGLE. Analytical, observational, and cross-sectional studies will be considered. All studies will undergo critical appraisal, data extraction, and synthesis. Data will be extracted using the JBI standardized data extraction tool for prevalence and incidence. Type and frequency of treatment and cytostatic agent will be extracted. The population will be described by age and gender. In addition, study methods and proportions of interest to the review question will be extracted. Pooled prevalence estimates will be calculated using a random effects model. Systematic review: PROSPERO CRD42020136706